Pre-eruptive excess volatiles and their relationship to effusive and explosive eruption styles in semi-plugged volcanoes - Utami, Sri Budhi; Andùjar, Juan; Costa, Fidel; Scaillet, Bruno; Humaida, Hanik; Carn, Simon (Frontiers in Earth Science, 2022)
Here we investigate the role of pre-eruptive magma storage conditions in controlling eruption styles at basaltic andesite volcanoes, and their relationship to monitoring data. Focusing our study on a cycle of explosive (1990, sub-Plinian) → effusive (2007, dome) → explosive (2014, sub-Plinian) eruptions from Kelud (Kelut) volcano, Indonesia, we conducted petrological analyses of the eruption products and phase equilibria experiments using a pumice and explored a range of temperatures, pressures, oxygen fugacity, and volatile contents. We show that we can reproduce the main mineral assemblage (plagioclase ± pyroxenes ± magnetite ± amphibole ± olivine), and phenocryst content (30-50 wt. %), of the magmas from the three eruptions at T = 975 ± 39°C, P = 175 ± 25 MPa, fO2 = NNO, and about 4-6 wt. % water in the melt (ca. 3 to 5 wt. %, and ca. 4 to 7 wt. % for the 1990 and 2014 eruptions, respectively). However, geothermobarometric results also indicate that some crystals of amphibole were sourced from higher pressures. Moreover, the high phenocryst content of the 2007 dome (~ 70 wt. %) likely resulted from slow magma ascent towards the surface alongside progressive degassing and re-equilibration at a lower volatile content (~1 wt. % water in the melt). Mass balance calculations on the sulfur budget of the 1990, 2007, and 2014 magmas, show that the explosive events contained an excess fluid phase at pre-eruptive conditions, and we propose that this led to their higher explosivity compared to the 2007 dome. The accumulation of excess fluids during decadal-long repose depends on how plugged (ability to passively release magmatic fluids) the volcanic system is prior to eruption. Such conditions could be estimated from monitoring records, including changes in gravity of the plumbing system over time.